Randomised control trials for the impact evaluation of development initiatives: a statistician’s point of view - Barahona, Carlos (2010)
This paper contains the technical and practical reflections of a statistician on the use of Randomised Control Trial designs (RCT) for evaluating the impact of development initiatives. It is divided into three parts. The first part discusses RCTs in impact evaluation, their origin, how they have developed and the debate that has been generated in the evaluation circles. The second part examines difficult issues faced in applying RCT designs to the impact evaluation of development initiatives, to what extent this type of design can be applied rigorously, the validity of the assumptions underlying RCT designs in this context, and the opportunities and constraints inherent in their adoption. The third part discusses the some of the ethical issues raised by RCTs, the need to establish ethical standards for studies about development options and the need for an open mind in the selection of research methods and tools.